2012
DOI: 10.3415/vcot-11-02-0019
|View full text |Cite
|
Sign up to set email alerts
|

Correction of craniodorsal coxofemoral luxation in cats and small breed dogs using a modified Knowles technique with the braided polyblend TightRope™ systems

Abstract: Clinical use of the Arthrex Mini TightRope and TightRope systems can be recommended for traumatic craniodorsal coxofemoral luxation in this novel application as short-term results are at least comparable to existing surgical techniques. Long-term follow-up studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
68
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(77 citation statements)
references
References 42 publications
7
68
2
Order By: Relevance
“…The reduction with Toggle pin can be disrupted by suture breaking between femoral head and acetabulum [29,32] . In a study, traumatic craniodorsal coxofemoral luxations in cats and small dogs were treated successfully by using using a modified Knowles technique, but mean weight of included dogs in this study was 15 kg [16] . In another study which compared toggle rod and suture anchor, it was reported that toggle rod constructs failed primarily by breakage of the suture at the rod eyelet and suture anchor constructs failed when the anchors pulled through the medial acetabular wall [17] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction with Toggle pin can be disrupted by suture breaking between femoral head and acetabulum [29,32] . In a study, traumatic craniodorsal coxofemoral luxations in cats and small dogs were treated successfully by using using a modified Knowles technique, but mean weight of included dogs in this study was 15 kg [16] . In another study which compared toggle rod and suture anchor, it was reported that toggle rod constructs failed primarily by breakage of the suture at the rod eyelet and suture anchor constructs failed when the anchors pulled through the medial acetabular wall [17] .…”
Section: Discussionmentioning
confidence: 99%
“…The luxation should be treated surgically; if there are complications such as hip dysplasia existence prior to trauma, femoral and/or acetabular avulsion fractures, intra articular fractures, arthrosis and conditions such as multiple orthopedic injuries or chronic luxation, closed reduction failure and extreme instability after reduction [5,8,12,13] . Techniques which are used for the surgical treatment of coxofemoral luxations can be categorized as extracapsular such as suture of a joint capsule (capsulorrhaphy) [3,5,12] , synthetic capsule technique [2,3,6,14] , transposition of the greater trochanter [2,5,6,12] , triple pelvic osteotomy [2,8] and intra capsular techniques such as Modified Knowles Toggle pin fixation [3,6,8,15,16] , Toggle rod stabilization [17,18] , trans acetabular pinning [2,6,19] transposition of the sacrotuberous ligament [20,21] . Additionally, flexible external fixation [8] , total hip replacement [22][23][24] and femoral head and neck osteotomy [2,25,26] can be also applied for the treatment of hip luxation.…”
Section: Introductionmentioning
confidence: 99%
“…Craniodorsal luxation is the most common luxation type diagnosed, occurring in 79% of luxations . Several techniques have been described to address coxofemoral luxation in the dog . No single method of luxation repair has proved to be superior in terms of outcome.…”
Section: Introductionmentioning
confidence: 99%
“…No single method of luxation repair has proved to be superior in terms of outcome. Short and long term reluxation rates for open reduction range from 0% to 28% …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation